Sweet syndrome with perifollicular involvement because of koebnerization from facial hair plucking. (2nd July 2021) - Flanagan, Kelly E.; Krueger, Steven; Amano, Shinya; Auerbach, Amanda; St. John, Jessica; Deng, April
Abstract: Sweet syndrome (SS), also known as acute febrile neutrophilic dermatosis, is an uncommon skin eruption characterized by fever, leukocytosis, and tender erythematous papules, nodules, and plaques. Histopathologically, SS lesions are characterized by marked superficial papillary edema with a dense neutrophilic infiltrate. SS is known to demonstrate both the Koebner phenomenon and pathergy. The majority of reported cases of these phenomena occur following significant cutaneous injury (e.g., biopsies, burns) rather than minor trauma such as pressure and friction. Here, we present the first known reported case of SS koebnerization secondary to minor grooming‐related hair plucking. In addition, this is also the first reported case to our knowledge of SS with perifollicular involvement on histopathology.